Network systems design : using network processors : Intel IXP version - Comer, Douglas Earl, 1949- (Upper Saddle River, N.J. : Pearson/Prentice Hall, 2004)
This book, broken into four major sections - quick review of basics, packet header formats, etc.; traditional protocol processing systems, network processors, and an example network processor - covers concepts, principles, hardware and software architectures that underly the design and implementation of network systems such as switches, bridges, routers, NAT boxes, firewalls, intrusion, detection systems, and load balancers. Topics covered include how to build network systems, the concepts of classification and classification languages, algorithms and data structures, issues in scaling a network processor and an overview of the Intel network processor. For professionals in the field of computer science, or anyone who has studied basic computer networking.
Includes bibliographical references (p. [497]-500) and index.
Keywords: Computer network architectures; Computer networks -- Equipment and supplies -- Design and construction; Computernetwerken; Internet; Network processors; System design